A individually randomized controlled trial comparing Healer-led vs. clinician- led training to improve personal protective equipment use among traditional healers in South Africa. - Carolyn M Audet; Tshegofatso Seabi; Taofik Oyekunle; Jennifer Hove; Ryan G Wagner (PLOS Global Public Health, 2024)
Like allopathic healthcare workers, healers are also exposed to patients' blood and body fluids. A widespread practice is the traditional "injection," in which the healer performs subcutaneous incisions to rub herbs directly into the bloodied skin, resulting in 1,500 blood exposures over their lifetime. We tested the impact of healer-led PPE training, staffed by trained traditional healers who reported using PPE during each risky clinical encounter vs. healthcare worker (HCW)-led PPE training sessions. We randomized 136 healers into one of the two study arms (67 in the healer-led group, 69 in the HCW-led group) and assessed the impact of trainer on PPE skills and use over a six-month period. All healers received one in-person day of didactic and practical training followed by three sessions at the healers' home. Participants were largely female (80%), averaged 51 years old, and practiced as a healer for an average of 17 years. Almost 44% either disclosed themselves as HIV+ or received a positive HIV test result at study initiation. Healers in the HCW arm showed equivalent PPE scores as those trained by traditional healers at baseline and at seven months. Healers in both arms self-reported high levels of glove use during"injections," with no statistical difference of use by study arm. When we assessed actual gloves and razor blades disposed of each month, a similar trend emerged. No one seroconverted during the study period. The need for PPE support among traditional healers cannot be ignored. Traditional healers can be trained to effectively disseminate PPE knowledge and skills to other traditional healers. With an estimated 200,000 traditional healers in South Africa, it is imperative that all of them have access to PPE training and supplies to prevent HIV, HCV, or HBV infections. Trial registration: ClinicalTrials.gov, NCT04440813. Registered 17 June 2020, https://clinicaltrials.gov/ct2/show/NCT04440813.